Understanding passenger satisfaction and expectations in free bus service based on socio-demographic characteristics in Johor and the Klang Valley, Malaysia - Zakaria, Husna; Md. Rohani, Munzilah; Mohd Pozi, Muhammad Fazreen (SINERGI, 2025)
Free bus service is known to serve passengers with the same goal as normal bus does. In fact, the implementation of free bus service acts as an alternative solution for those who have financial limitations. To keep a high satisfaction level of passengers regardless of various backgrounds, it is important for the free bus providers to maintain the quality of their service. Therefore, this study aims to understand the relationship between socio-demographic characteristics and the satisfaction level and expectation of passengers on free bus services allocated in Klang Valley and Johor, Malaysia. A survey was conducted among the free bus users to collect data on their socio-demographic characteristics and their experiences with the service quality offered. According to the survey, teens and single people were the primary passengers of the free bus service. Moreover, passengers who had low income, no driving license, and no vehicles were also more likely to use the service. The overall satisfaction level of passengers was high (mean score > 3.6), indicating that the service quality provided by the free bus service provider met the expectations of passengers. However, no evidence was found from this study to relate socio-demographic factors with satisfaction level.